Use of Imaging Spectroscopy for Mapping and Quantifying the Weathering Degree of Tropical Soils in Central Brazil - Gustavo M. M. Baptista; Rodrigo S. Corrêa; Perseu F. dos Santos; José S. Madeira Netto; Paulo R. Meneses (Applied and Environmental Soil Science)
The purpose of this study was to test the feasibility of applying AVIRIS sensor (Airborne Visible/InfraRed Imaging Spectrometer) for mapping and quantifying mineralogical components of three Brazilian soils, a reddish Oxisol in São João D'Aliança area (SJA) and a dark reddish brown Oxisol and Ultisol in Niquelândia (NIQ) counties, Goiás State. The study applied the spectral index RCGb [kaolinite/(kaolinite + gibbsite) ratio] and was based on spectral absorption features of these two minerals.The RCGb index was developed for the evaluation of weathering degrees of various Brazilian soils and was validated by the analysis of soil samples spectra imaged by AVIRIS and checked against laboratory mineralogical quantification (TGA:Thermal Gravimetric Analysis). Results showed to be possible mapping and quantifying the weathering degree of the studied soils and that the two selected areas presented different weathering degrees of their soils even for a same soil type.